(untitled) (Journal of Industrial and Mechanical Engineering, 2024)
The history of piping manufacturing by the metalworking industry and its associated cost traditionally lies in a production paradigm based on the identification of preparation, presentation, welding and validation operations through non-destructive testing. These activities are usually manual and depend largely on the qualification of the workforce. Concern then arises about the testing of alternative technologies and their economic impact. In this context, the approval of a new methodology that minimizes the use of elbows represents a proposal that, if not technically and economically reasoned, would not be accepted by the market. For this reason, it is the purpose of this work, with a focus on the economic scalability of the 3D curved proposal, to provide the industry with the context for analyzing the results of an innovative technology with the potential to improve up to 61.2% of the usual cost.